2001
DOI: 10.1292/jvms.63.751
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Classical Swine Fever Virus Associated with Defective Interfering Particles Containing a Cytopathogenic Subgenomic RNA Isolated from Wild Boar.

Abstract: ABSTRACT. Classical swine fever virus (CSFV) strain WB82, isolated from a wild boar in 1982, induced a distinct cytopathic effect (CPE) in primary swine testicle cell culture and in most of the porcine cell lines. This strain of CSFV was found to be composed of two biotypes, cytopathogenic (cp) CSFV, as a minor population, and noncytopathogenic (noncp) CSFV, as a major population. The noncp CSFV (designated strain WB82/E + ) was obtained by biological cloning, and it showed the exaltation of Newcastle disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Interestingly, all cp CSFV field isolates analyzed so far consist of a non-cp CSFV helper virus together with a cp viral subgenome that lacks the genomic region encoding the structural proteins as well as the NS proteins N pro , p7, and NS2 (2,36,51). In addition, several studies reported on the generation of helper virus-independent (HVI) cp CSFV.…”
mentioning
confidence: 99%
“…Interestingly, all cp CSFV field isolates analyzed so far consist of a non-cp CSFV helper virus together with a cp viral subgenome that lacks the genomic region encoding the structural proteins as well as the NS proteins N pro , p7, and NS2 (2,36,51). In addition, several studies reported on the generation of helper virus-independent (HVI) cp CSFV.…”
mentioning
confidence: 99%
“…Interestingly, all cp CSFV field isolates analyzed so far consist of a noncp CSFV strain together with a viral subgenome. With the exception of subgenome cpBW1, which lacks 4,746 nucleotides (nt) (24), all other subgenomes are characterized by a common internal deletion of 4,764 nt, resulting in fusion of the translation initiation codon to the first codon of the NS3 gene (1,24,35). It could be demonstrated that the deletion of these CSFV subgenomes represents the genetic basis for expression of large amounts of NS3 and cytopathogenicity.…”
mentioning
confidence: 99%
“…The respective subgenomes are defective interfering particles (DI) dependent on the presence of a helper virus for packaging (37). Such strains were isolated not only from domestic pig and wild boar but also from tissue culture cells in which noncp CSFV was passaged (1,35,39).To study various aspects of RNA recombination, we recently established the first in vivo RNA recombination system for pestiviruses which allowed the efficient generation of cp BVDV strains in cell culture (17). Here, we report on an analogous approach for CSFV.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A rare cytopathogenic (cp) form can occur spontaneously in cell culture [70] and has also been found in wild boar [71]. Its significance in CSFV pathogenesis is unknown.…”
Section: A Few Salient Features Of the Structure Composition And Funmentioning
confidence: 99%